Monte Carlo investigation of mixed normal and relaxor ferroelectrics - Laosiritaworn Y. (2014)
In this work, Monte Carlo simulation was used to model the ferroelectric behavior of mixed normal and relaxor ferroelectrics using the single polarization-flip algorithm. The purpose is to investigate the dependence of ferroelectric properties on the field frequency, the temperature and the normal ferroelectric concentration in the relaxor ferroelectrics. Results obtained from both static and dynamic simulation stress the significant effect of the larger ferroelectric interaction caused by the normal ferroelectric contents. For instance, with increasing normal ferroelectric concentrations, the transition between zero and nonzero polarization phases shifts to a higher temperature due to stronger ferroelectric interaction. In addition, the stronger ferroelectric interaction also causes less polarization switching, where the hysteresis gets larger in size at low frequencies, but smaller at high frequencies. This strong ferroelectric interaction also shifts the frequency at maximum phase-lag between polarization and field signal to a lower frequency. These results are in good agreement with experiments, where applicable. Copyright © Taylor & Francis Group, LLC.